Strategi Pelaksanaan Kegiatan Profil Pelajar Pancasila dalam Membentuk Kreativitas Peserta Didik SMAN 2 Pandeglang Tahun 2024 - Maoliya Siti Nurfalida; Delia Ardianti; Putry Maharani Adillah; Siti Alikha Allyasari; Salma Nurul Izzah; Zahira Hasna Tsalitsa; Nurfuzi Damayanti; Tantri Mugi Utami Rosandhi; Cahya Harenia; Rendi Raihan (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to identify strategies for implementing Pancasila Student Profile activities to support the development of student creativity at SMAN 2 Pandeglang. The method in this research is a qualitative method using a descriptive approach. This data was collected through literature study, which includes searching various written sources such as journals, books and articles as scientific references to build a strong theoretical basis. Apart from that, direct observations were also carried out in the school environment to understand the situation and interactions related to the implementation of the project to strengthen the Pancasila Student Profile (P5). The research results show that effective P5 implementation strategies in encouraging student creativity include three main stages: planning, implementation, and evaluation. The planning stage involves forming a facilitator team, determining themes, and preparing teaching tools. At the implementation stage, activities begin with the introduction of P5 and optimizing the implementation process. Meanwhile, the evaluation stage was carried out to assess the effectiveness of P5 activities involving teachers and students.